Characterization of aerosols in Beijing during severe aerosol loadings. (October 2015) - Chen, Hao; Cheng, Tianhai; Gu, Xingfa; Wu, Yu
Abstract: Severe aerosol pollutions in China significantly impact radiative forcing of climate at regional and global scales. Until now, the uncertainties in net climate forcing from severe aerosol pollutions in China are substantial, largely due to the lack of detailed knowledge of radiative properties of severe aerosol pollutions. Here the characteristics of aerosols under severe aerosol pollution days (APs) in Beijing are studied by analyzing the ground-based radiance measurements during the period from 2002 to 2014. We show that the mean single scattering albedo (SSA) values increase by 0.03–0.06 (7%) in APs, and the mean asymmetry (ASY) parameter values increase by 0.03–0.04 (6%) for the four wavelengths of 440–1020 nm. The atmospheric forcing of the APs is 2 times higher than that in other days. Contrary to the RF values, the radiative forcing efficiencies in the APs are 38% lower than those in the other days. Larger values of SSA and ASY under APs represent larger presence of more scattering aerosols and irregular-sized aerosols such as dust and non-absorbing fine mode particles. These particles are also verified by the much lower radiative forcing efficiency values. Analyses are applied on the dataset of the APs over Beijing, to group them into four discrete clusters. The two fine-size absorbing aerosols show larger mean atmospheric radiative forcing values (152.5 W/m 2 and 184.5 W/m 2 respectively) and forcing efficiency values (83.5 W/m 2 and 108.5 W/m 2 respectively). The non-absorbing aerosols and coarse aerosols exert large planetary cooling (−86.7 W/m 2 and −77.3 W/m 2 ) and low atmospheric heating effect. Highlights: Properties of aerosols under aerosol pollution days (APs) in Beijing are studied. The mean SSA and ASY increase by 7% and 6% in APs compared to those in other days. The atmospheric forcing of the APs are 2 times higher than that in other days. Four aerosol types are obtained via cluster analysis of the APs data in Beijing.